2013
DOI: 10.1080/17457300.2013.835324
|View full text |Cite
|
Sign up to set email alerts
|

Burden, distribution and impact of domestic accidents in a semi-urban area of coastal Tamil Nadu, India

Abstract: The objectives of this study are to determine the prevalence of domestic accidents, describe the factors associated with domestic accidents and assess the medical and economical consequences of domestic accidents. Community-based cross-sectional study was conducted in a semi-urban area of Tamil Nadu during February 2013. A total of 3947 study participants were interviewed using a structured questionnaire. Study variables included were socio-demography, housing conditions, epidemiological factors, medical and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…A cross-sectional household survey conducted in Pondicherry reported 0.2% of all deaths to be caused by drowning 20. One hospital-based study from Vellore attributed 20% of all injury-related deaths to drowning,19 while a second from Tamil Nadu reported no drowning deaths to have occurred over a study period of 1 year 23. A review of autopsy records for women aged 12–49 years from one hospital site in Mangalore attributed drowning to 5% of all deaths 15.…”
Section: Resultsmentioning
confidence: 99%
“…A cross-sectional household survey conducted in Pondicherry reported 0.2% of all deaths to be caused by drowning 20. One hospital-based study from Vellore attributed 20% of all injury-related deaths to drowning,19 while a second from Tamil Nadu reported no drowning deaths to have occurred over a study period of 1 year 23. A review of autopsy records for women aged 12–49 years from one hospital site in Mangalore attributed drowning to 5% of all deaths 15.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies in urban and semi-urban areas showed a wide prevalence from 1.7% to 12.7%. 4,5,20,21 Similarly, in rural population the range was from 4.8% -14.6%. 1,16,[22][23][24] The higher values in rural population could be attributed to the dearth of knowledge regarding household safety measures whereas the present study had a prevalence in the higher side because of the inclusion period of reported accidents in past one year compared to three and six months in other studies.…”
Section: Discussionmentioning
confidence: 95%
“…(1) The problem is more grave in developing countries, particularly in rural areas, shanty towns or informal dwellings. (2,3) Every domestic accident brings a varying measure of distress to the victim as well as the family members. The consequences may be disastrous, both for the individual and the society when the accident results in permanent disability, as the victim loses his earning capacity and may not be able to enjoy a normal active life.…”
Section: Introductionmentioning
confidence: 99%